Cardiac sources of cerebral embolism in people with migraine. (24th October 2020) - De Giuli, V.; Grassi, M.; Locatelli, M.; Gamba, M.; Morotti, A.; Bonacina, S.; Mazzoleni, V.; Pezzini, D.; Magoni, M.; Monastero, R.; Padovani, A.; Pezzini, A.
Abstract : Background and purpose: Whether the reported association between migraine with aura (MA) and cardioembolic stroke may be explained by a higher rate of atrial fibrillation (AF) or by other potential cardiac sources of cerebral embolism remains to be determined. Methods: In the setting of a single centre cohort study of consecutive patients with acute brain ischaemia stratified by migraine status, the association between AF as well as patent foramen ovale (PFO) and migraine was explored. Results: In all, 1738 patients (1017 [58.5%] men, mean age 67.9 ± 14.9 years) qualified for the analysis. Aging was inversely associated with migraine, whilst women had a >3‐fold increased disease risk (odds ratio [OR] 3.82, 95% confidence interval [CI] 2.58–5.66). No association between AF and history of migraine or its pathogenic subtypes was detected. Conversely, migraine was associated with PFO, both in the entire cohort (OR 1.84, 95% CI 1.07–3.16) and in patients aged ≤55 years (OR 2.21, 95% CI 1.16–4.22). This association was significant for MA (OR 2.92, 95% CI 1.32–6.45 in the entire cohort; OR 2.92, 95% CI 1.15–7.41 in patients aged ≤55 years) and in women (OR 8.23, 95% CI 2.06–32.77), but not for migraine without aura. Conclusions: In patients with brain ischaemia migraine is not associated with AF. Conversely, there is a probable relation between migraine, especially MA, and PFO in patients who are younger and have a more favourable vascular risk factor profile, and in women. Abstract : The biological mechanisms underlying the association between migraine and ischemic stroke remain unclear. Growing evidence suggests that cerebral micro embolization of cardiac origin might trigger migraine attack in the context of increased cortical hyperexcitability, thereby contributing to the stroke risk in migraineurs. The results of this study indicate that the relation between cardio embolism and migraine is unlikely to be explained by atrial fibrillation (AF), but rather, by interatrial right‐to‐left shunt (patent foramen ovale, PFO). This seems especially true for the subtype migraine with aura, for younger subjects who have a more favorable vascular risk factor profile, and for women.